The dynamics of heroin use; implications for intervention. Issue 12 (1st December 2001) - Millar, T; Craine, N; Carnwath, T; Donmall, M
Abstract : STUDY OBJECTIVE: To use a readily available dataset to detect periods of epidemic change and to examine the progression of heroin epidemics in different geographical areas. To consider the implications of epidemic change for strategies to tackle drug misuse. DESIGN: Comparison of trends in new treatment demand, observed incidence, and age specific population rates for treated heroin users in two geographical areas. PARTICIPANTS: Heroin users recorded to have sought treatment. MAIN RESULTS: The areas studied seem to show differences with respect to trends in new treatment demand, incidence of heroin use and distribution of age specific population rates; indicating that they may be at different epidemic stages. CONCLUSIONS: These analyses show how areas may differ with respect to epidemic progression of heroin use. It is essential that government strategies, and local responses to these, should be cognisant of these dynamics.